Julián López, La ilusión de los mamíferos (Altre Modernità, 2018)
Julián López, La ilusión de los mamíferos(Buenos Aires, Literatura Random House, 2018, pp. 172, ISBN 978-987- 769-005-7)por Emilia Perassi